Etude Evolutive des Résultats des Elèves de Sixième Année des Humanités Commerciales et Administratives aux Examens d’Etat « Cas des Ecoles de la Ville de Kisangani de 1999 à 2006 » - Depse, BAENDAENDA SHINDANI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
It should be remembered that the problem of school evaluation is not a new fact: all teachers have always tried to assess or evaluate their pupils, either before learning (Predictive Assessment) or during learning (Formative evaluation), ie at the end of the apprenticeship (Summative Evaluation).For a long time, these types of assessments have focused more on knowledge than on other taxonomic skills. For many years, parents, teachers and school authorities have complained of the gradual and continual decline in the intellectual level of students, especially low percentages of success in state examinations.Indeed, in the Democratic Republic of Congo (DRC), the Ministry of Primary, Secondary and Professional Education (EPSP), through its technical departments, designs items, organizes tests, evaluates and deliberates. This system has the effect of guaranteeing uniform criteria for success or failure, delimiting abuses and fraud, and awarding degrees by category (options).As a result, students' success in state exams is a real stimulus for the public authorities. It also for school boards, teachers and students. It requires everyone to have the right supervision, respect for the programs and seriousness in the exam preparation. This has consequences that benefit the entire school. For example, a better selection of pupils in the lower classes, a selective recruitment of teachers and an improvement of the management of the competing establishment always to a better success of students in state examinations.